AMY-101 as complement C3 inhibitor for periodontitis therapy: mechanisms, efficacy, and clinical translation - Li, Jialun; Xu, Zhi; Ayre, Wayne Nishio; Liu, Xiaohan (Frontiers in Immunology, 2025)
Periodontitis is a chronic inflammatory disease characterized by gingival inflammation, alveolar bone resorption, and periodontal tissue destruction. Complement activation, particularly through the C3 component, plays a critical role in the inflammatory processes underlying periodontitis. AMY-101, a selective inhibitor of complement C3, has demonstrated significant potential in modulating complement activity and mitigating periodontal inflammation. This study comprehensively evaluates AMY-101’s effects through in vitro, preclinical, and clinical studies. Mechanistic investigations revealed that AMY-101 effectively suppresses pro-inflammatory cytokines and matrix metalloproteinases (MMPs), reducing tissue destruction. Preclinical models confirmed AMY-101’s ability to improve clinical parameters such as probing pocket depth, attachment loss, and bone preservation. Moreover, clinical trials demonstrated AMY-101’s safety and efficacy in reducing gingival inflammation and bleeding without serious adverse events. These findings highlight AMY-101’s therapeutic potential for periodontitis and broader applicability in other complement-driven inflammatory diseases.